Statistical Approach in Analyzing Fuel Efficiency of Diesel SUVs in Indonesia Using MATLAB - Canda Lesmana Ginting; Asaeli Tongoni Lase; Farrah Anis Fazliatul Adnan; Jong Soo Rhee; Dianta Ginting (International Journal of Innovation in Mechanical Engineering and Advanced Materials, 2025)
The scarcity of fossil fuels and the rising environmental concerns make improving fuel efficiency in the automotive sector a critical focus. Diesel Sport Utility Vehicles (SUVs) in Indonesia, known for their high fuel consumption, significantly contribute to these challenges. This research ad-dresses the problem by investigating the factors influencing fuel efficiency in diesel SUVs availa-ble in the 2024 Indonesian market. The primary objective is to analyze the impact of engine torque, vehicle weight, and engine capacity on fuel consumption. To achieve this, we employed MATLAB as a tool for statistical analysis, using specific algorithms such as linear regression, box plot, and correlation methods to model and evaluate the data. The study found that vehicle weight and engine capacity show a strong positive correlation with fuel consumption, indicating that larger engines and heavier vehicles consume more fuel. In contrast, engine torque was found to have a weaker correlation, suggesting that factors like aerodynamics and transmission efficiency may play a more significant role. These results provide valuable insights for manufacturers in de-signing more fuel-efficient SUVs and for consumers making informed purchasing decisions. Ulti-mately, this research contributes to the development of more sustainable transportation solu-tions by highlighting the importance of optimizing vehicle design and engine specifications to re-duce fuel consumption in the near term.